Four Tier Diagnostic Tes Instrument To Identify Misconceptions For Grade Ix Junior High School Students In Jember Regency - Kurniawan Pandu Wicaksono; Ika Priantari; Aulya Nanda Prafitasari (Bioeducation Journal, 2021)
Misconception is an event where there is a fallacy of the concept received by students after following a learning process, this accepted concept is not in accordance with existing scientific studies. One of the most common materials is material related to human heredity material class IX junior high school. The development of a Four-Tier Diagnostic Test instrument is one of the efforts in identifying the misconception of the material. This study aims to find out the validity level of the Four-Tier Diagnostic Test instrument as a good measuring tool in identifying the misconception of class IX junior high school human heredity material located in Jember Regency. This study involved 29 learners from Muhammadiyah Junior High School 4 Tanggul for instrument validity test. This type of research is descriptively quantitative using purposive sampling methods. Based on the analysis of expert validity tests obtained validity rate of 84.16% (very valid), instrument validity test value of 92.30% valid questions and 7.69% of invalid questions, reliability test value obtained 12 questions have reliability value of 0.785, difficulty tests obtained results of 75% of moderate problems, 8.30% of easy problems, and 16.60% of difficult problems, and different power tests obtained results of 33.33% of sufficient questions, 41.66% about good, 16.66% about good, and 8.33% bad.